Work stress among managers of business organizations in Bangladesh - Islam, Md. Asadul; Jantan, Amer Hamzah Bin; Bashir, Md. Abdul; Masud, Md. Sohel; Roy, Banarupa (Globeedu Group, 2017)
This paper aims to identify the sources and levels of work stress experienced by frontline, middle and senior managers within business organizations in Bangladesh. Six factors are considered as the major antecedents of work stress namely role overload (qualitative), role overload (quantitative), role conflict, role ambiguity, responsibility for others and career development. Study has used a cross-sectional survey to collect quantitative data from 457 respondents in particular three managerial positions, frontline, middle and senior from 36 randomly selected business organizations operating in private sector of Bangladesh. Results have revealed that 80.40% of participants experience moderate levels of work stress in their workplace. Career development and responsibility for others are identified as the most significant sources of work stress in Bangladeshi business organizations. Role conflict and role ambiguity have been found as stressors causing reasonably least amount of work stress among the participants. Since there has been no study, previously, identifying the sources and levels of work stress in Bangladeshi business organisations, the significance of this research lies in its highlighting of the specific factors causing work stress among the business managers in this country.